A case study on quality improvement of connecting rod assembly line using Six Sigma DMAIC cycle. (20th October 2020) - Kumar, Sunil; Brahma, Gayatri; Kaur, Prabhkiran; Gupta, Brijesh Kumar
To have a successful growth in business and an enhanced competitive position, application of quality improvement equipment is one important dimension of operational performance. In present case study, the purpose is to reduce the rejection of manufactured connecting rods by using Six Sigma approach. To overcome the barriers of the customer demands the methodology of Six Sigma define, measure, analyse, improve, and control (DMAIC) cycle has been applied in structuring of the process analysis of connecting rod assembly line. A software, viz., Minitab17 has been used to solve the problems for the ongoing processes running in the firm. After collecting the data from the process layout in real-time, the identification of different causes affecting the process were studied and consequently pinpointed the opportunities for reformation. Initially, it was found that there were around 13.99% defects and after the implementation of Six Sigma DMAIC cycle the defects were reduced to 10.12%. So, quality improvement was achieved by a reduction of 3.87% defects. The process capability as well as the process performance improved according to the Six Sigma norms.